Short-Term and Long-Term Outcomes in Mid and Low Rectal Cancer With Robotic Surgery - Chen, Jingwen; Zhang, Zhiyuan; Chang, Wenju; Yi, Tuo; Feng, Qingyang; Zhu, Dexiang; He, Guodong; Wei, Ye (Frontiers in Oncology, 2021)
Objective To investigate the risk factors for postoperative complications and anastomotic leakage after robotic surgery for mid and low rectal cancer and their influence on long-term outcomes. Methods A total of 641 patients who underwent radical mid and low rectal cancer robotic surgery at Zhongshan Hospital Fudan University from January 2014 to December 2018 were enrolled in this study. The clinicopathological factors of the patients were collected. The risk factors for short-term outcomes of complications and anastomotic leakage were analyzed, and their influences on recurrence and overall survival were studied. Results Of the 641 patients, 516 (80.5%) underwent AR or LAR procedures, while 125 (19.5%) underwent the NOSES procedure. Only fifteen (2.3%) patients had stoma diversion. One hundred and seventeen patients (17.6%) experienced surgical complications. Anastomotic leakage occurred in 44 patients (6.9%). Eleven patients (1.7%) underwent reoperation within 90 days after surgery. Preoperative radiotherapy did not significantly increase anastomotic leakage in our study (7.4% vs. 6.8%, P=0.869). The mean postoperative hospital stay was much longer with complication (10.4 vs. 7.1 days, P<0.05) and leakage (12.9 vs. 7.4 days, P<0.05). Multivariate analysis showed that male sex (OR=1.855, 95% CI: 1.175-2.923, P<0.05), tumor distance 5 cm from the anus (OR=1.563, 95% CI: 1.016-2.404, P<0.05), and operation time length (OR=1.563, 95% CI: 1.009-2.421, P<0.05) were independent risk factors for complications in mid and low rectal cancer patients. The same results for anastomotic leakage: male sex (OR=2.247, 95% CI: 1.126-4.902, P<0.05), tumor distance 5 cm from the anus (OR= 2.242, 95% CI: 1.197-4.202, P<0.05), and operation time length (OR= 2.114, 95% CI: 1.127-3.968, P<0.05). The three-year DFS and OS were 82.4% and 92.6% with complication, 88.4% and 94.0% without complication, 88.6% and 93.1% with leakage, and 87.0% and 93.8% without leakage, respectively. The complication and anastomotic leakage showed no significant influences on long-term outcomes. Conclusion Being male, having a lower tumor location, and having a prolonged operation time were independent risk factors for complications and anastomotic leakage in mid and low rectal cancer. Complications and anastomotic leakage might have no long-term impact on oncological outcomes for mid and low rectal cancer with robotic surgery.